The Pentingnya Etika Informasi di Tengah Imperium Datakarasi dalam Terang pemikiran Luciano Floridi : The Importance of Information Ethics in the Midst of the Datakarasi Empire in the Light of Luciano Floridi's Thoughts - Emanuel, Yohanes; Pandor, Pius (Jurnal Filsafat Indonesia, 2025)
The main focus of this paper is to examine the role of information ethics in the midst of the data empire, based on the thinking of Luciano Floridi. Information ethics is important to study and develop further due to the rapid development of technology. Technological advances have expanded the scope of information ethics issues beyond the spread of hoaxes to also focuses on privacy and data protection for everyone as part of the study of information ethics. In recent decades, a new phenomenon has emerged due to technological advancements: the rise of data based power or the data-driven empire, where data serves as a tool to acquire and maintain power, particularly in social, economic, and political decision-making. This situation also drives information ethics as a fundamental aspect of safeguarding the data security of every individual. Luciano Floridi, an Italian philosopher, attempts to explain the importance of information ethics in the midst of technological advancements. Technological advancements have led society to live in an infosphere, a digital ecosystem that demands moral responsibility in processing, distributing, and utilizing information, according to Floridi. Technological advancements and data dominance also bring ethical challenges, according to Floridi, such as privacy violations, information manipulation, and technological access disparities. Thus, information ethics becomes a fundamental aspect as a controller of technological progress to prevent the emergence of a data driven empire that harms the entire society without access. These ethical challenges will be examined in this paper, which includes two main questions: what is meant by a data monopoly? How can the concept of information ethics in Luciano Floridi's thinking be applied to address the challenges of a data monopoly? This paper will be analyzed using a qualitative literature review method.